PENGUJIAN KUALITAS AIR ASAM TAMBANG PADA TAMBANG BATUBARA PT. Bukit Asam Tbk – Tanjung Enim - Rembah, Rina (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2015)
Mine drainage was problem in mining aktivity at activ periode and mine closure. And will be enviroment issue from mine drainage is water quality, what is Pontentially Acid Forming or Non Acid Forming. For to know water quality will be forming, as the firts step is understanding about stone geochemical characteristic. Stone of behavior can be knew base on geochemical characteristic by step testing are static test with testing sulfure total, pH paste, pH NAG, ABA methode and verification with kinetic test by Free Draining Column Leach Test with physic and chemical testing, also mineralogy testing with X-RD for to know mineral composition in stone. Base on characteristic result can be get stone type potentially acid forming/ PAF and non acid forming/NAF. Then water quality test as leachate stone PAF/NAF by kinetic quality test. From this research, result of type the stone are PAF and NAF, where PAF is high capacity with NAPP value 88,64 kg H2SO4/ton and pH NAG 2,42 with kinetic test result showen pH 2,18 in acid zone. And for NAF with NAPP value -0,78 kg H2SO4/ton and pH NAG 6,81 with kinetic test result showen pH 7,53 in netral zone.